Canthin-6-One Accelerates Alpha-Synuclein Degradation by Enhancing UPS Activity: Drug Target Identification by CRISPR-Cas9 Whole Genome-Wide Screening Technology - Yuan, Ning-Ning; Cai, Cui-Zan; Wu, Ming-Yue; Zhu, Qi; Su, HuanXing; Li, Min; Ren, JiaoYan; Tan, Jie-Qiong; Lu, Jia-Hong (Frontiers in Pharmacology, 2019)
Parkinson's disease (PD) is the second most common neurodegenerative disorder characterized by the accumulation of protein aggregates (namely Lewy bodies) in dopaminergic neurons in the substantia nigra region of the brain. Alpha-synuclein (α-syn) is the major component of Lewy bodies in PD patients, and impairment of the ubiquitin-proteasome system has been linked to its accumulation. In this work, we developed a tetracycline–inducible expression system, with simultaneous induced expression of α-syn-EGFP and a bright red fluorescent protein marker (mCherry) to screen for potential compounds for degrading α-syn. we identified canthin-6-one as an α-syn lowering compound which promoted both wild type and mutant α-syn degradation in an ubiquitin-proteasome-system (UPS) dependent manner. By CRISPR/Cas9 genome-wide screening technology, we identified RPN2/PSMD1, the 26S proteasome non-ATPase regulatory subunit 1, as the targeting gene for pharmacological activity of canthin-6-one. Finally, we showed that canthin-6-one up-regulates PSMD1 and enhances UPS function by activating PKA.